Assessment of Personality from a New Perspective: Characterix Personality Types Inventory - Yilmaz, Olcay; Yildirim, Aykut; Yucedag, Dilek (International Journal of Scientific Research and Management (IJSRM), 2018)
Even though it is taught and used in many countries all over the world there is a lack of emprical research and psychometric assesment on Eneagram classification system of personality. This study aimed to contribute the this literature and present some evidence as well as developing a valid and reliable inventory. Research sample consisted of 21140 young and adults and data were randomly divided into two groups with an aim of conducting principal component analysis and confirmatory factor analysis for each data set. As a result the inventory formed with 72 items and it can be said that it has high item-factor loadings, and each dimension measures the characteristics intended to measure while explaining the variance at an acceptable level. Many of the findings indicated a good fit. Sufficient internal consistency values were obtained in all dimensions. All these findings indicate that the inventory has sufficient reliability and validity values.